Perbedaan Kesiapsiagaan Operator SPBU dalam Menghadapi Kebakaran dengan Kapasitas Operasional yang Berbeda - Ria Nurjanah; Daru Lestantyo; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Emergency preparedness is part of disaster management process to ensure that actions to be taken immediately after a disaster occur are appropriate, fast and effective actions. Gas station is a infrastructure provided by a distributor of fuel oil for the wider community to meet fuel needs. Gas station operators have a high risk because most fires occur during refueling. The purpose of this research is to analyze differences in preparedness with different operational capacities, analyze the corelation of knowledge, attitudes and fire protection facilities to operator preparedness in the face of fires at Undip Gas Station and Meteseh Gas Station. The type of research used is quantitative by using a cross-sectional study. The sample used in this study is the entire population with a total of 37 people. Questionnaire and observation checklist were used as the instruments of this research. The observation sheet was used to check the suitability of existing fire protection facilities with the prevailing standards in Indonesia. The statistical analysis used was the chi-square test, mann whitney and sign-test. The results showed that there were no differences in gas station operator preparedness with different operational capacities (p=0.588), there was a relation between attitude and operator preparedness (p=0.025), no relation between knowledge (p=value 1,000) and fire protection facilities (p=0.833) with operator preparedness. Researcher suggested holding training and simulations for operators regarding fire preparedness, the use of fire extinguishers, and inspection of fire extinguishers.